2014
DOI: 10.1016/j.ejpal.2014.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral problems and depressive symptomatology as predictors of child-to-parent violence

Abstract: The number of complaints filed by parents against their children nationwide has increased dramatically, particularly since 2005. The aim of this study was to examine whether young offenders who had been charged for violence against their parents presented different psychological problems from youngsters charged with other types of offence and non-offenders. Data from 231 adolescents of both sexes aged 14 to 18 years and living in the Basque Country (Spain) were analyzed. Of these, 106 were offenders and the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
70
1
24

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(113 citation statements)
references
References 42 publications
13
70
1
24
Order By: Relevance
“…The present study extended prior research findings (Ibabe, Arnoso, & Elgorriaga, 2014;Khan & Cooke, 2013) by examining aggression perpetrated by two mental health samples and the use of weapons. Prior research that had examined family aggression among juvenile offenders found that the majority of the sample had used a weapon (i.e., heavy or sharp objects) to perpetrate aggression (Khan & Cooke, 2013), while research that examined clinic-referred youth found no weapon use (Nock & Kazdin, 2002).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The present study extended prior research findings (Ibabe, Arnoso, & Elgorriaga, 2014;Khan & Cooke, 2013) by examining aggression perpetrated by two mental health samples and the use of weapons. Prior research that had examined family aggression among juvenile offenders found that the majority of the sample had used a weapon (i.e., heavy or sharp objects) to perpetrate aggression (Khan & Cooke, 2013), while research that examined clinic-referred youth found no weapon use (Nock & Kazdin, 2002).…”
Section: Discussionsupporting
confidence: 54%
“…A prior study on 231 adolescents from the community (n=125, non-offender) and prison (n=106, offender) found that 16% and 73% of them, respectively, perpetrated physical aggression toward their parents (Ibabe, Arnoso, & Elgorriaga, 2014). A similar study which examined a sample of 606 clinic-referred adolescents reported that 12.2% had perpetrated physical aggression toward one of their parents.…”
Section: Introductionmentioning
confidence: 96%
“…La mayor parte de los investigadores (Rechea y Cuervo, 2009;González-Álvarez et al 2011;Ibabe y Jaureguizar, 2012;Ibabe, Arnoso, Elgorriaga, 2014) reconocen que un tanto por ciento muy elevado de los menores agresivos -7 de cada 10 para Rechea y Cuervo (2010), 6 de cada 10 según Romero et al (2005)-presentan problemas de violencia general, interaccionado estrechamente con otros menores problemáticos, con pertenencia (70,6 % de los casos) a grupos de iguales desadaptados (Rechea y Cuervo, 2010), manteniendo relaciones de amistad con iguales violentos (40,6 %), y presentando en muchos casos (el 53,4 %) carreras delictivas más amplias (Romero et al, 2005). Otros llegan aún más lejos al afirmar que los infractores que agreden a sus padres tienen más problemas conductuales fuera del hogar, incluso, que los infractores que cumplen medida por otros delitos (Ibabe y Jaureguizar, 2012; Ibabe, Arnoso y Elgorriaga, 2014).…”
Section: Modelos Sistémicosunclassified
“…De todo lo anterior podemos concluir que la VFP es un fenómeno complejo, de creciente incidencia y etiología múltiple y variada (Ibabe y Jaureguizar, 2012;Ibabe, Arnoso, Elgorriaga, 2014;Sánchez, 2008;Pueyo Andrés, 2006;Cottrell y Monk, 2004). Dicha complejidad parte de que no hay un solo perfil de maltratador, como tampoco un solo perfil de familia, influyendo factores muy diversos que interaccionan en contextos ecológicos diferentes, si bien no tan distintos de los que explican otras formas de agresión juvenil.…”
Section: Conclusiónunclassified
“…These numbers have risen annually. Furthermore, the most frequently committed juvenile crimes are theft, extortion, assault and battery, murder, fraud, arson, and larceny [36]. According to records of the General Directorate of Criminal-Records and Statistics for the year 2008, among the cases brought to juvenile and juvenile high crimes courts (which are arranged according to crime type, gender, and age), the most frequent crimes were theft, fraud, looting, and extortion; and the second most frequent types of crimes were ones related to bodily harm such as mutilation, murder, torture, persecution, and organ trafficking.…”
Section: Background Of Research Problemmentioning
confidence: 99%